Foreign bodies in ear, nose and throat (Predictions and management) - Ghosh, P (Springer India, 1999)
Management of a patient with foreign body (FB) in the ENT areas is an art. FB in the respiratory tract is fraught with respiratory obstruction and even death, rarely though, especially in infants and children, if not intervened in time. Fair prediction can be made as to the site and side of lodgment of FB in lower respiratory tract depending on the age of the patient so that timely intervention on the involved side can be made without undertaking haphazard scopy.